Leaf senescence of Christella hispidula (Decne.) Holttum throughout climatic seasons in an urban park with a remnant of the Atlantic Forest (Research, Society and Development, 2022)
The term senescence is used mainly for plants to define genetically programmed degenerative physiological changes. Leaf senescence is the result of internal and external environmental signals as well as information on leaf age. Christella hispidula (Decne.) Holttum is a species of fern characterized by its adaptation ease and consequent broad occupation of different environments. The aim of the present study was to investigate the phenology of C. hispidula in a remnant of the Atlantic Forest to gain knowledge on abiotic and biotic factors associated with leaf senescence throughout the seasons. Multiple regression analysis was used to estimate correlations between leaf senescence and both the occurrence of herbivory and presence of sori in the population studied. Positive correlations were found with these two variables. Senescence increased significantly with each new sign of herbivory on the plant (p = 0.46) and with the emergence of sori on the plant (p = 0.02). The multiple coefficients of determination (R2= 0.47) explained approximately 47% of the dependence of senescence on herbivory and sori. The findings reveal that the seasons exert an influence on leaf senescence in C. hispidula.